Impact Of Seed Treatment With Plant Growth Regulators And Nutrients On Alleviation Of Salinity Stress In Tomato Under In Vitro Conditions (Applied Biological Research, 2016)
An in vitro experiment was conducted with two tomato (Solanum  lycopersicum) genotypes (PKM 1 and TNAU THCO 3) to assess  alleviation of salinity stress by seed treatment using plant growth  regulators and nutrients under laboratory conditions. Salt stress was  imposed at 60 mM concentration by using NaCl. Plant growth  regulators like indole acetic acid (100 ppm), gibberellic acid (1 mM),  benzyl aminopurine (50 ppm), salicylic acid (2 mM), ascorbic acid (100  ppm) and salts potassium chloride (1%) and calcium chloride (0.5%)  were used to alleviate salinity effects. The study revealed that among  ameliorants used, gibberellic acid showed significantly premier  observations like highest germination percentage (76.7 and 86.7%),  tolerance index (62 and 68.2%) and alpha amylase activity (11.02  and 11.55 μg maltose g-1 sample) in PKM 1 and TNAU THCO 3,  respectively. Catalase activity was high (32.65 and 36.25 μg H2O2 g-1 min-1) in salicylic acid treatment. Hybrid tomato TNAU THCO 3  responded well to PGRs and nutrients than variety PKM 1.
Keywords: α-amylase; catalase; salinity; tomato; stress tolerant index; vigour index